2008
DOI: 10.1159/000159122
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Outcome of Congenital Left Ventricular Aneurysms and Diverticula in an Adult Population

Abstract: Objectives: We sought to investigate the prevalence and clinical outcome of congenital left ventricular aneurysms (LVAs) and diverticula (LVD) in a large adult population. Methods: We retrospectively studied the left ventricular angiograms of 12,271 consecutive patients undergoing cardiac catheterization at our institution and analyzed the medical records of the patients. Results: The overall prevalence of LVA/LVD was 0.76% (94 patients): there were 42 patients with LVA (0.34%) and 52 patients with LVD (0.42%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
56
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 22 publications
1
56
0
1
Order By: Relevance
“…8 The majority of these patients are free of symptoms. However, some patients may present with potentially life-threatening clinical conditions due to the presence of these disorders, such as ventricular tachyarrhythmias, congestive heart failure, and systemic embolic complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 The majority of these patients are free of symptoms. However, some patients may present with potentially life-threatening clinical conditions due to the presence of these disorders, such as ventricular tachyarrhythmias, congestive heart failure, and systemic embolic complications.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients may present with cardiac arrhythmias, embolic complications, or heart failure. 8 There are only few observational case reports and small series on congenital left ventricular aneurysms and diverticula in the medical literature. [9][10][11][12][13][14] The association of this abnormality with ventricular tachyarrhythmia was reported in 1971 by Maloy et al 9 However, very little is known on the clinical outcome of these patients to date.…”
mentioning
confidence: 99%
“…[1] The prevalence of congenital ventricular diverticulum has been reported to be 0.42% among adult patients undergoing ventriculography after presenting to cardiac clinics with various symptoms. [2]…”
Section: Discussionmentioning
confidence: 99%
“…3 The prevalence of congenital left ventricular outpouchings was 0.76% in a retrospective study of 12 271 adults undergoing left ventricular catheterization and found to have normal coronary arteries. 4 In that study, 5 of 79 patients, all of them with diverticula, suffered embolic stroke attributed to the diverticulum during a follow-up period of 56 months, suggesting that outpouchings present a significant risk of stroke. Other complications included arrhythmia and rupture.…”
mentioning
confidence: 84%